The Relativity of Mitigating Factors in Corruption Crime Verdicts: A Philosophical and Juridical Study Based on Substantive Justice and Judicial Legal Reasoning - Yogi Yasa Wedha; Made Hendra Wijaya; Putu Sekarwangi Saraswati (Fakultas Hukum, Universitas Warmadewa, 2025)
The relativity in applying mitigating factors in corruption case verdicts often leads to legal uncertainty and inconsistency with the principles of substantive justice. This study aims to analyze how mitigating factors influence substantive justice by employing John Rawls’ theory of justice and to evaluate judicial legal reasoning through Neil MacCormick’s theory. Employing a normative juridical approach, this research conducts an in-depth analysis of legal literature and relevant theories. The results reveal that the variable application of mitigating factors may lead to inconsistencies between judicial rulings and the principles of substantive justice, especially when social impacts are overlooked. Moreover, the absence of structured standards leads to variations in judicial reasoning, causing public dissatisfaction with the judicial system. This study recommends the development of more stringent and measurable guidelines, as well as enhanced knowledge and training for judges to integrate substantive justice theories and legal reasoning into practice, thereby improving transparency, consistency, and the legitimacy of court rulings.